Unidades de conservação e territórios Quilombolas: desafios, sobreposições de interesses e conciliação de direitos em Minas Gerais - Raquel Faria Scalco (2019)
Creating Protected Areas (PAs) is an important approach to ensure the conservation of natural resources and the protection of biodiversity. Nevertheless, the method in which PAs are created and/or managed often causes a series of conflicts between communities and management bodies. This is the situation of some indirect used protected areas of Minas Gerais, created in inhabited areas, or also areas used by quilombolas2 communities, which rely on natural resources for their survival and for the reproduction of their social practices. Therefore, with the creation of PAs, several activities developed by these communities were restricted, limited and criminalized. It is important to consider that quilombolas communities were firstly responsible for the conservation of such areas before the creation of PAs. This situation has engendered conflicts between management bodies and quilombolas communities, which offer proposals for downgrading, downsizing and degazettement of indirect used protected areas in Minas Gerais. Those proposals may benefit external agents interested in implementing economic development projects, since they already exert pressure on the traditional territories of quilombolas communities and on the PAs. Thus, this research was developed from questioning the possibility of reconciling two fundamental rights guaranteed in laws: the right to balanced environment, which rely its most important instrument on the creation of PAs; and the cultural and territorial rights of quilombolas communities. In this sense, this research was developed with the aim of understanding how the overlapping of protected areas and traditional territories of quilombolas communities can influence the status of the biodiversity protection of Minas Gerais, by proposals for PAs downgrading, downsizing and degazettement. A survey of these overlapping cases was carried out in Minas Gerais, identifying seven cases in which this situation occurs. Therefore, it was possible to understand the legal aspects related to the creation of PAs and quilombolas territories, as well as the legal treatment for overlap cases between these territories, and which strategies are used to manage conflicts resulting from these overlaps by quilombolas communities and PAs' managing bodies, considering the different legal rights involved. The methodological approach used in this study counts on bibliographic research, cabinet research, field works and realization of semi-structured interviews. Techniques of document and content analysis were used for data examination. As a result, it is necessary to reaffirm that the presence of quilombolas communities in indirect used PAs can contribute to the conservation of natural resources, provided that agreements and partnerships must be established between those who are involved, and the compliance with instruments that regulate the use of natural resources within PAs. Thus, when dealing with traditional peoples and communities that live or use resources of indirect used PAs, the best alternative is to ensure more flexible management, in order to avoid major losses arising from downgrading, downsizing and degazettement of the area and the pressure that the capital exerts on these territories.